Neuroradiology training in EU: international survey of 31 countries within UEMS frame - Pizzini, Francesca B.; Sasiadek, Marek; Tanzi, Francesco; Ricci, Paolo (Insights into imaging, 2020)
Objective To assess the current framework of interventional and diagnostic neuroradiology in Europe Methods The UEMS (European Union of Medical Specialists) Section of Radiology and the subspecialty UEMS Division of Neuroradiology collected by e-mail a survey on the situation of diagnostic and Interventional Neuroradiology’ training and practice in Europe. The questionnaire was sent to the national delegates from 31 UEMS member countries, belonging to the European Union, the European Economic Area and the Council of Europe. In case of uncertain or discordant replies, the survey envisaged the involvement of neuroradiology scientific societies’ experts for providing a decisive answer. Results A formal post-residency training in diagnostic and interventional neuroradiology is provided respectively by 12/31 and 20/31 of the European countries. Currently, for becoming neuroradiologist in a country without fellowship program, a radiologist should (1) get subspecialty credits, (2) follow training inside national or international neuroradiology departments, or (3) perform the main reporting activity in neuroradiology. In nearly 2/3 of the States included in the survey, the neurointerventional procedures are provided by radiologists (22/31) and in the most frequent scenario a specific training in neurovascular is required to all radiologist or non-radiologist candidates (18/31). Conclusions The European framework of neuroradiology’s training and practice that emerged through this survey is fragmented, but there is an increasing attention by European scientific societies and institutions to create a common path of training and practice that can guarantee high educational and patient care standards.